Elucidation of the anti-autophagy mechanism of the Legionella effector RavZ using semisynthetic LC3 proteins - Yang, Aimin (eLife, 2017)
Autophagy is a conserved cellular process involved in the elimination of proteins and organelles. It is also used to combat infection with pathogenic microbes. The intracellular pathogen Legionella pneumophila manipulates autophagy by delivering the effector protein RavZ to deconjugate Atg8/LC3 proteins coupled to phosphatidylethanolamine (PE) on autophagosomal membranes. To understand how RavZ recognizes and deconjugates LC3-PE, we prepared semisynthetic LC3 proteins and elucidated the structures of the RavZ:LC3 interaction. Semisynthetic LC3 proteins allowed the analysis of structure-function relationships. RavZ extracts LC3-PE from the membrane before deconjugation. RavZ initially recognizes the LC3 molecule on membranes via its N-terminal LC3-interacting region (LIR) motif. The RavZ α3 helix is involved in extraction of the PE moiety and docking of the acyl chains into the lipid-binding site of RavZ that is related in structure to that of the phospholipid transfer protein Sec14. Thus, Legionella has evolved a novel mechanism to specifically evade host autophagy. DOI: http://dx.doi.org/10.7554/eLife.23905.001